Does Online Viral Marketing Contribute to the Tourists’ Intention to Visit a Destination? - Rahyuniati Setiawan, Ratih Hurriyati , Lili Adi Wibowo (International Journal of Advanced Science and Technology, 2020)
The background of this study is the decline in tourist visits to Sabda Alam Water Park in Garut. Viral marketing plays an important role in raising brand awareness and may affect tourists’ intention to visit a tourism object. The purpose of this study was to examine the effect of viral marketing on brand awareness and tourist visit intentions. To this end, an explanatory survey was conducted on a sample of 100 visitors to Sabda Alam Water Park selected using a proportionate random sampling technique. Data analysis was performed using path analysis using SPSS 21. The results of this study indicate that viral marketing has a significant positive effect on brand awareness. It was also revealed that brand awareness and viral marketing had a positive influence on tourists’ visiting intention.